Frequency of Early Fusion of Bone in the Lumbosacral Spine: Radiographic Evidence of Bridging Bones Following Pedicle Screw Fixation - Ahmed, Hafiz Kabeer; Saghir, Aamir; Ghouri, Amna (Biological and Clinical Sciences Research Journal, 2025)
Pedicle screw fixation is a widely used surgical procedure for the management of lumbosacral fractures. Despite its frequent application, limited evidence exists regarding its effectiveness in achieving early bone fusion. Objective: To determine the rate of early bone fusion following pedicle screw fixation of lumbosacral fractures and to evaluate the impact of patient factors, including ASA class and smoking status, on fusion outcomes. Methods: A descriptive cross-sectional study was conducted at a tertiary care hospital in Karachi, Pakistan, from January to May 2025 after ethical approval. Patients aged 18–65 years with ASA class <IV who underwent pedicle screw fixation of the lumbosacral spine were included. Participants were followed for three months to assess early bone fusion radiographically. Descriptive statistics were presented as mean (SD) for continuous variables and frequency (%) for categorical variables. Binary logistic regression was performed to adjust for confounders, with adjusted odds ratios (aOR) and 95% confidence intervals (CI) reported. Results: A total of 139 patients were enrolled, with a mean age of 40.70 ± 8.97 years. The cohort comprised 84 females (60.43%) and 55 males (39.57%). Early bone fusion was achieved in 124 patients (89.21%). Smoking status was independently associated with reduced odds of early bone fusion, with lower fusion rates observed among current smokers (aOR: 0.12, 95% CI: 0.03–0.45) and ex-smokers (aOR: 0.14, 95% CI: 0.04–0.51) compared with non-smokers. Similarly, patients with ASA class II (aOR: 0.16, 95% CI: 0.04–0.63) and class III (aOR: 0.04, 95% CI: 0.01–0.32) had significantly lower odds of early fusion compared to ASA class I. Conclusion: Pedicle screw fixation demonstrated a high rate of early bone fusion in lumbosacral fractures. However, smoking and higher ASA class were identified as independent risk factors for reduced fusion, emphasizing the importance of patient optimization and smoking cessation in improving postoperative outcomes.